The migration of fishers as a driver of change in local fishers' identity. The case of Imraguen fishermen in Mauritania. Issue 3 (3rd July 2021) - Ly, Djibril; David, Gilbert
ABSTRACT: Once an isolated territory difficult to access, the Banc d'Arguin has gradually opened up to international marketing channels for fishing products despite its status as a marine protected area. For the past thirty years or so, the park's rich fishery resources have continued to attract the covetousness of Mauritanian migrant fishermen and fishermen from countries of the West African sub-region. Neighbourhood with the Imraguen over the decades has not been without consequences on their fishing practice, their mentality, their behaviour, their economy and their identity in crisis of recognition. This article aims to analyse the changes that have taken place within this Imraguen fishing community, particularly due to the presence of migrant fishermen who have settled in the park since the mid-1980s.